Dissociation of disease onset, progression and sex differences from androgen receptor levels in a mouse model of amyotrophic lateral sclerosis - Doris Tomas (Nature Portfolio, 2021)
Abstract Amyotrophic lateral sclerosis (ALS) is an adult-onset neurodegenerative disorder caused by loss of motor neurons. ALS incidence is skewed towards males with typically earlier age of onset and limb site of onset. The androgen receptor (AR) is the major mediator of androgen effects in the body and is present extensively throughout the central nervous system, including motor neurons. Mutations in the AR gene lead to selective lower motor neuron degeneration in male spinal bulbar muscular atrophy (SBMA) patients, emphasising the importance of AR in maintaining motor neuron health and survival. To evaluate a potential role of AR in onset and progression of ALS, we generated SOD1G93A mice with either neural AR deletion or global human AR overexpression. Using a Cre-LoxP conditional gene knockout strategy, we report that neural deletion of AR has minimal impact on the disease course in SOD1G93A male mice. This outcome was potentially confounded by the metabolically disrupted Nestin-Cre phenotype, which likely conferred the profound lifespan extension observed in the SOD1G93A double transgenic male mice. In addition, overexpression of human AR produced no benefit to disease onset and progression in SOD1G93A mice. In conclusion, the disease course of SOD1G93A mice is independent of AR expression levels, implicating other mechanisms involved in mediating the sex differences in ALS. Our findings using Nestin-Cre mice, which show an inherent metabolic phenotype, led us to hypothesise that targeting hypermetabolism associated with ALS may be a more potent modulator of disease, than AR in this mouse model.